Messenger App-Based Information Provision for Promoting Social Participation to Enhance Well-Being Among Community-Dwelling Adults: Randomized Controlled Trial - Atsushi Nakagomi; Noriyuki Abe; Yu-Ru Chen; Kazushige Ide; Shuhei Kobayashi; Masamichi Hanazato; Katsunori Kondo (JMIR Publications, 2024)
BackgroundEngaging in social activities, interacting with peers, and participating in community events may promote health and well-being. Recently, interventions leveraging information and communications technology have emerged as potent tools for promoting social connections and well-being. Particularly, messenger apps have become an integral part of our daily lives, facilitating communication, information dissemination, and social interaction. However, there remains a gap in the literature regarding the utilization of widely adopted messenger apps for this purpose. ObjectiveThis study aimed to evaluate the impact of messenger app-based information provision aimed at promoting social participation on the enhancement of subjective well-being among Japanese community-dwelling adults. MethodsA 2-arm, parallel-group randomized controlled trial was conducted from October 2022 to January 2023 in the Kashiwa-no-ha campus area, Japan-an urban community with active local events. A total of 358 community-dwelling adults who use messenger apps daily were recruited for the study. Of these, 235 (65.6%) participants completed the follow-up survey. Participants were randomly assigned to either the intervention group, receiving the health benefits of social participation and information about local events or spots via a messenger app, or the control group, receiving general health information. The primary outcome was subjective happiness after the intervention, measured on an 11-point scale ranging from 0 (Unhappy) to 10 (Happy). Secondary outcomes included life satisfaction, meaning of life, purpose in life, and participation in local events. The outcomes were analyzed with t tests (2-tailed) and multivariable regression based on the intention-to-treat method. ResultsAfter the intervention, the intervention group reported a mean happiness score of 7.7 (SD 1.7), while the control group reported a score of 7.5 (SD 2.0), with no statistically significant difference (P=.40). Multivariable linear regression analysis adjusted for baseline outcome values and covariates showed that the coefficient of the intervention for life satisfaction was 0.30 (95% CI -0.07 to 0.68; P=.12), while that for meaning of life was 0.33 (95% CI -0.03 to 0.70; P=.07). There was no significant difference in event participation rates between the 2 groups during the study period (P=.22). However, 82.2% (102/124) of the intervention group acknowledged the utility of the event information provided. ConclusionsMessenger app-based information provision did not yield a significant increase in subjective happiness, while there was a positive but not significant trend in life satisfaction. The findings underscore the need for more intensive intervention in future studies to harness the potential of digital interventions. Trial RegistrationUMIN Clinical Trials Registry UMIN000049047; https://tinyurl.com/2zzrrae8